Multi band gap electronic structure in CH3NH3PbI3 - Ong, Khuong P. (2019)
Organo-lead halide perovskite solar cells represent a revolutionary shift in solar photovoltaics, introducing relatively soft defect containing semiconductors as materials with excellent charge collection for both electrons and holes. Although they are based on the nominally simple cubic perovskite structure, these compounds are in fact very complex. For example, in (CH3NH3)PbI3 the dynamics and ensuing structural fluctuations associated with the (CH3NH3)+ ions and the interplay with the electronic properties are still not fully understood, despite extensive study. Here, using ab-initio calculations, we show that at room and higher temperature, the rotation of CH3NH3 molecules can be viewed as effectively giving local structures that are cubic and tetragonal like from the point of view of the PbI3 framework, though in fact having lower symmetry. Both of these structures are locally polar, with sizable polarization, ~10 μC/cm2 due to the dipoles on the organic. They become energetically degenerate in the volume range, V ~ 250 Å3/f.u–265 Å3/f.u. We also find very significant dependence of the band gap on the local structure. This type of transition is analogous to a transition between two ferroelectric structures, where in-spite of strong electron phonon coupling, there is strong screening of charged defects which can lead to enhanced mobility and charge collection. The results provide insights into the enhanced light absorption near the band edge and good charge collection in this material.